A new approach to very high lithium salt content quasi-solid state electrolytes for lithium metal batteries using plastic crystals. Issue 44 (28th October 2019) - Al-Masri, Danah; Yunis, Ruhamah; Zhu, Haijin; Jin, Liyu; Bruce, Peter; Hollenkamp, Anthony F.; Pringle, Jennifer M.
Abstract : The combination of a highly conductivity plastic crystal with a very high concentration of lithium salt results in a promising new "plastic crystal in salt" electrolyte for lithium metal batteries. Abstract : While the high energy density of lithium metal has long been a strong driver for the development of lithium metal batteries, harnessing the full theoretical capacity in a safe, practical device requires significant advances in electrolyte design. The use of quasi-solid state electrolytes can be greatly beneficial for increasing safety, suppressing the growth of lithium dendrites and prolonging cell lifetime. Organic ionic plastic crystals (OIPCs) are a unique class of disordered solid that can support high ionic conductivities and lithium ion mobility. Until recently, OIPCs were used primarily as matrix materials and incorporated only low dopant concentrations of lithium salts. Here we report a very high lithium content electrolyte containing 90 mol% lithium bis(fluorosulfonyl)imide, Li[FSI], combined with 10 mol% of a conductive pyrrolidinium FSI-based OIPC. The resultant quasi-solid state electrolyte achieves a conductivity of 0.24 mS cm −1 at 30 °C, supports stable lithium electrochemistry and has a very good lithium ion transference number of 0.68. Symmetrical Li|Li cell cycling is demonstrated at 0.1 mA cm −2 for 100 hours. This showcases a new approach for designing safer quasi-solid state electrolytes with high lithium content and excellent electrochemical and transport properties.